Effects of dietary protein and fat level and rapeseed oil on growth and tissue fatty acid composition and metabolism in Atlantic salmon (Salmo salar L.) reared at low water temperatures - Karalazos, Vasileios; Bendiksen, Eldar Asgard; Dick, James R; Bell, J Gordon (Aquaculture Nutrition, 2007)
A 12 week feeding trial was conducted to elucidate the interactive effects of dietary fat and protein contents and oil source on growth, fatty acid composition, protein retention efficiency (PRE) and β-oxidation activity of muscle and liver in Atlantic salmon (Salmo salar L.) at low water temperatures (4.2 oC). Triplicate groups of Atlantic salmon (initial weight 1168 g) were fed six isoenergetic diets formulated to provide either 390 g kg-1 protein and 320 g kg-1 fat (high protein (HP) diets) or 340 g kg-1 protein and 360 g kg-1 fat (low protein (LP) diets); within each dietary protein/fat level crude RO comprised 0, 30 or 60% (R0, R30, R60, respectively) of the added oil. After 12 weeks the overall growth and FCR were very good for all treatments (TGC; 4.76 (±0.23), FCR; 0.85 (±0.02)). Significant effects were shown due to oil source on SGR and TGC only. The liver and muscle FA compositions were highly affected by the graded inclusion of RO. The PRE was significantly affected by the dietary protein level, while no significant effects were shown in total β-oxidation capacity of liver and muscle. The results of this study suggest that more sustainable, lower protein diets with moderate RO inclusion can be used in Atlantic salmon culture at low water temperatures with no negative effects on growth and feed conversion, no major detrimental effects on lipid and fatty acid metabolism and a positive effect on protein sparing.